Coma in thrombotic thrombocytopenic purpura. (23rd November 2010) - de Jong, F J; te Boekhorst, P A W; Dippel, D W J; Jacobs, B C
Abstract : Thrombotic thrombocytopenic purpura (TTP) is characterised by a thrombotic, haemolytic microangiopathy leading to microvascular occlusion, haemolysis and ischaemic dysfunction of various organs including the brain. TTP may present with a variety of neurological symptoms, including headache, focal deficits, seizures and coma. The authors describe a 55-year-old man presenting with abdominal pain and rapidly progressive deterioration into coma without focal neurological deficits or seizures. A concomitant, transient, rapid increase in blood pressure raised the suspicion of a hypertensive crisis. Yet, our patient did not improve after vigorous treatment with antihypertensives. Brain imaging excluded a hypertensive leucoencephalopathy. Despite the absence of a disintegrin and metalloproteinase with a thrombospondin type 1 motif member 13 (ADAMTS13) deficiency, the diagnosis idiopathic TTP was made after excluding secondary causes of TTP. Upon treatment with plasma exchange, corticosteroids and vincristin our patient gradually improved. On discharge to a rehabilitation centre he was awake and alert, had minor cognitive deficits and a mild proximal tetraparesis consistent with a critical illness poly(neuro)myopathy.